Pemberdayaan Santri melalui Program Kursus Menjahit di Pondok Pesantren Al-Bayan Rangkasbitung - Intan Rahmadhani Fitri; Isna Rahmawati (Jurnal Pemberdayaan Masyarakat, 2022)
Sewing courses can be seen as a solution to reduce the unemployment rate. Al-Bayan Rangkasbitung Islamic Boarding School holds a sewing course program that supported by the Vocational Training Center (BLK) for santri as a provision to prepare for the future. The purpose of this study is to find out the process and results of empowering santri through a sewing course program at the Al-Bayan Rangkasbitung Islamic Boarding School. This study uses a qualitative research approach with descriptive analysis, data collection techniques using observation, interviews and document analysis. Data analysis was carried out by data reduction, data presentation, as well as verification and drawing conclusions. The results of the study show that the process of empowering santri carried out by the Al-Bayan Rangkasbitung Islamic Boarding School can be seen through awareness raising, capacity building and empowerment. The process of empowering santri at the Al-Bayan Rangkasbitung Islamic Boarding School was said to be successful because the santri were able to meet basic needs, reach productive sources and participate in development and decision-making processes.